DESIGN OF MIXED-USE AREA IN LEUWI PANJANG BUS TERMINAL BASED ON TRANSIT-ORIENTED DEVELOPMENT (TOD), BANDUNG CITY, INDONESIA - Firdaus Dwi Putra Rustiandi; Asep Yudi Permana; Risya Maryam Al Haq (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2021)
AbstractLeuwi Panjang Terminal of Bandung City is a terminal with an A-type category in the city of Bandung. This terminal is one of the proposed Transit Oriented Development in Bandung Urban Mobile Project 2031 programs. Listed in the BUMP 2031 program, the Leuwi Panjang Terminal area will be equipped as a public transportation transit, monorail. Based on the existing criteria, the Leuwi Panjang terminal doesn’t fulfill the criteria as a Transit Oriented Development area, including inadequate facilities, the circulation systems that are not mutually integrated and the unavailability of signage makes visitors confused about their activity paths, and the stiffness of pedestrians and cyclists to move around in this area. This study discusses the architectural design recommendations of the TOD area that fill the TOD standards of the Leuwi Panjang Terminal. The method used is by conducting area studies, activity studies, and circulation studies. The study is analyzed and processed to produce a synthesis and application to the design to fulfill the TOD criteria and government regulations. Keywords: Transit-Oriented Development, Integration, Terminal, Of Bandung City.